Hybrid Cryptographic Solution to Overcome Drawbacks of RSA in Cloud Environment - Yadav, Rupal; Singh, Kaptan; saxena, Amit (International Journal of Computer Sciences and Engineering, 2020)
Cloud Computing is the technology, which is growing more and more in the area of information technology. It is a big platform to deliver services to user. It provides with the benefit of storage, configuration, resources and sharing and all this is possible in cloud environment. Data is outsourced by the owner to store it on cloud because they have to serve there user at every possible stage. Presented work establishes security approach to secure and enhance the security of data at every step. Purpose of proposed work is to prevent from intruders and attackers and from sniffing messages. Proposed work is implemented using hybrid system (RC6+AES) and MD5 to calculate integrity. Using essential measurements like integrity, confidentiality, encryption, authentication, and authorization security in achieved in presented work.